Experience evaluations for human–computer co-creative processes – planning and conducting an evaluation in practice - Anna Kantosalo; Sirpa Riihiaho (Connection Science)
In human–computer co-creativity, humans and creative computational algorithms create together. Too often, only the creative algorithms and their outcomes are evaluated when studying these co-creative processes, leaving the human participants to little attention. This paper presents a case study emphasising the human experiences when evaluating the use of a co-creative poetry writing system called the Poetry Machine. The co-creative process was evaluated using seven metrics: Fun, Enjoyment, Expressiveness, Outcome satisfaction, Collaboration, Ease of writing, and Ownership. The metrics were studied in a comparative setting using three co-creation processes: a human–computer, a human–human, and a human–human–computer co-creation process. Twelve pupils of age 10–11 attended the studies in six pairs trying out all the alternative writing processes. The study methods included observation in paired-user testing, questionnaires, and interview. The observations were complemented with analyses of the video recordings of the evaluation sessions. According to statistical analyses, Collaboration was the strongest in human–human–computer co-creation, and weakest in human–computer co-creation. Ownership was just the opposite: weakest in human–human–computer co-creation, and strongest in human–computer co-creation. Other metrics did not produce statistically significant results. In addition to the results, this paper presents the lessons learned in the evaluations with children using the selected methods.